2021
DOI: 10.1111/gean.12308
|View full text |Cite
|
Sign up to set email alerts
|

A Micro‐Econometric Store Choice Model Incorporating Multi‐ and Omni‐Channel Shopping: The Case of Furniture Retailing in Germany

Abstract: Online retailing and multi-/omni-channel shopping are gaining in importance. However, there is a significant lack of research focused on incorporating online shopping into models of spatial shopping behavior. The present study aims (1) to construct a store choice model which includes both physical and online stores as well as the opportunity for omnichannel shopping, and ( 2) to identify the main drivers of spatial shopping behavior given the availability of both channels. Based on a representative survey, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 63 publications
0
21
0
12
Order By: Relevance
“…Then the Delphi method was used to collect experts' opinions and determine the basic indicators (Brady 2015) to understand the basic situation of online purchasing platforms and the constituent factors of online item purchase (Wang 2014;Chen et al 2022). A further goal was to understand how online and offline consumption will be influenced by its related factors, leading to different choice results (Wieland 2021). The research results were eventually summarized and adjusted according to the literature on the online furniture market (Zhao 2016;Li 2022;Wang and Yang 2022) and the current state of buying by replanning the influencing factors and using the indicator system of the existing literature as a reference.…”
Section: Consumption Influence Factor Index Determination Methodsmentioning
confidence: 99%
“…Then the Delphi method was used to collect experts' opinions and determine the basic indicators (Brady 2015) to understand the basic situation of online purchasing platforms and the constituent factors of online item purchase (Wang 2014;Chen et al 2022). A further goal was to understand how online and offline consumption will be influenced by its related factors, leading to different choice results (Wieland 2021). The research results were eventually summarized and adjusted according to the literature on the online furniture market (Zhao 2016;Li 2022;Wang and Yang 2022) and the current state of buying by replanning the influencing factors and using the indicator system of the existing literature as a reference.…”
Section: Consumption Influence Factor Index Determination Methodsmentioning
confidence: 99%
“…With respect to store choice, store size increases and travel time (driving, public transport, or walking) reduces the likelihood of a store being chosen, which is in line with previous store choice studies. Using a store choice and expenditure model, Wieland ( 2021a , b , 2023 ) has combined the aforementioned approaches of channel and store choice. Results have shown that channel choice is mainly influenced by shopping attitudes, place of residence, and age of the consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The econometric strategy in this study is based on the modeling approach outlined in Wieland ( 2021a , b , 2023 ), which incorporates an adaptation of the hurdle model (Mullahy 1986 ) applied to (spatial) shopping behavior. The hurdle model is a special kind of count data model which was designed for excess of zeros in the dependent variable.…”
Section: Modeling Approach and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations